2020
DOI: 10.1172/jci137110
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor-associated macrophages and granulocytic myeloid-derived suppressor cells augments PD-1 blockade in cholangiocarcinoma

Abstract: Figure 1. TAMs are the predominant source of PD-L1 in CCA. (A) Representative images (left and middle panels) of PD-L1 (brown staining, black arrowhead) plus CD68 (red staining, red arrowhead) coimmunostaining (n = 33) and PD-L1 (brown staining) plus CK-19 (red staining) coimmunostaining (n = 18) in human resected CCA specimens. Percentage of patients with positive PD-L1/CD68 costaining and PD-L1/CK19 costaining, respectively (right panel). Scale bars: 40 μm. (B) Histograms show expression of PD-L1 + macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(192 citation statements)
references
References 58 publications
3
164
0
1
Order By: Relevance
“…Here it is shown that GR-1 hi MDSCs are morphologically granulocytic, confirmed by their expression of Ly6G, and GR-1 int MDSCs are monocytic like cells morphologically and express high levels of Ly6C. This is consistent with other reports of GR-1 and Ly6C/G expression [37,38]. MDSCs are potent suppressor cells, and their presence in various pathological conditions has been proven to cause damaging effects and worsen prognosis in patients [39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here it is shown that GR-1 hi MDSCs are morphologically granulocytic, confirmed by their expression of Ly6G, and GR-1 int MDSCs are monocytic like cells morphologically and express high levels of Ly6C. This is consistent with other reports of GR-1 and Ly6C/G expression [37,38]. MDSCs are potent suppressor cells, and their presence in various pathological conditions has been proven to cause damaging effects and worsen prognosis in patients [39].…”
Section: Discussionsupporting
confidence: 91%
“…Their phenotype and functions have been studied in detail only more recently [ 31 , 32 ]. Whilst some studies use CD11b+, GR-1+ phenotype to describe MDSCs in different disease models [ 33 , 34 , 35 ], others define granulocytic MDSCs as Ly6Ghi and monocytic MDSCs as Ly6Chi [ 36 , 37 ]. Here it is shown that GR-1 hi MDSCs are morphologically granulocytic, confirmed by their expression of Ly6G, and GR-1 int MDSCs are monocytic like cells morphologically and express high levels of Ly6C.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pharmacological inhibition of PI3K-γ, which is highly expressed on myeloid cells, shifted TAMs from a M2-like immunosuppressive phenotype to an inflammatory M1-like phenotype in the murine 4T1 mammary carcinoma and B16 melanoma models ( 115 ). Paradoxically, reducing TAMs can result in a compensatory increase of MDSCs ( 116 , 117 ). However, this effect can be overcome by blocking both TAMs and gMDSCs, which augments the efficacy of PD-1 blockade in a mouse model of cholangiocarcinoma ( 116 ) and bolsters chemotherapy in a mouse model of PDAC ( 117 ).…”
Section: Simulating a “Small” Immune Microenvironmentmentioning
confidence: 99%
“…Some of the drugs have also been used in clinical trials, either as stand-alone therapies or in combination with immunotherapy or non-immune-based established cancer therapies, including chemotherapy and radiotherapy. Several studies have demonstrated that combining MDSC inhibition with CBI yields significantly better control of tumor growth compared to monotherapy (Christmas et al 2018, Clavijo et al 2019, Loeuillard et al 2020, Orillion et al 2017. For example, in a clinical trial of advanced melanoma patients treated with all-trans retinoic acid, an inhibitor of MDSC, in combination with the CTLA-4 monoclonal antibody ipilimumab, patients had significantly reduced levels of PD-L1, IL-10, and IDO (indoleamine 2,3dioxygenase)-expressing MDSC (NCT02403778) (Tobin et al 2018).…”
Section: Therapeutic Targeting Of Mdsc Is Essential For Optimizing Camentioning
confidence: 99%